English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I really dont understand how to answer equations so if anyone can explainit it would be nice ; )

2007-02-01 15:30:29 · 11 answers · asked by ohsbabygirl22 1 in Science & Mathematics Mathematics

11 answers

I assume you need to solve for the "x variable in the equation.

First: eliminate the parenthesis --- rewrite the expression on the right, excluding parenthesis...

64 = 3x - 11 + 2x - 2

Sec: combine "like" terms...

64 = 3x + 2x - 11 - 2
64 = 5x - 13

Or, 5x - 13 = 64

Third: isolate "5x" on one side --- add "13" to both sides (when you move a term to the opposite side, always use the opposite sign)...

5x - 13 + 13 = 64 + 13
5x = 77

Fourth: isolate "x" on one side --- divide both terms by "5"...

5x/5 = 77/5
x = 77/5

P.S. The solution doesn't have to be written in decimal form, unless your teacher aks you to do so.

2007-02-01 17:51:01 · answer #1 · answered by ♪♥Annie♥♪ 6 · 0 0

All you do is get rid of the brackets and simplify the equation:

64 = 3x - 11 + 2x -2
64 = 3x +2x - 11 - 2
64 = 5x - 13

Now, rearrange the equation so you have coefficients on one side (anything that ONLY has a number) and variables on the other (x is a variable). Another way of looking at it is to add 13 to both sides of the equation so you can get rid of the -13 on the right side.

64 + 13 = 5x - 13 + 13
77 = 5x
x = 77/5

2007-02-01 15:46:01 · answer #2 · answered by Jackson G 1 · 0 0

Apparently, you want to find the value of x.
64 = (3x - 11) + (2x - 2)
Step One:
Flip flap the equation;
(3x - 11) + (2x - 2) = 64
Step Two:
Remove the parenthesis;
3x -11 + 2x - 2 = 64
Step Three:
Combine like terms;
5x -13 = 64
Step Four:
Add +13 to both sides of the equation;
5x - 13 + 13 = 64 + 13
Step Five:
Perform algebraic addition;
5x + 0 = 77
5x = 77
Step Six:
Divide both sides of the equation by 5;
x = 77 / 5
or
x = 15.4
Please memorize the steps!
Good luck.
Email me if you need some more explanations.

2007-02-01 15:47:23 · answer #3 · answered by Anonymous · 0 0

it is easy...

the first thing you should do is eliminate the parenthesis, as there is no minus before the parenthesis, its content wouldn't be affected so the first step would be the following:
64=3x-11+2x-2

The next step is solve all the independent terms (the numbers without x) and the variables (numbers with x) on each side of the equation:
64=5x-13

Then you should pass all the similar terms to the same side of the equation, but if it was a sum in the original side of the equation, it will pass as its contrary to the other side.

This means:
64+13=5x

77=5x

Then you pass the 5 (that was multipying the x) to divide the 77 in order that the x is alone.

77/5=x
or
x=77/5
x= 15.4

The value for x is 15.4

2007-02-01 15:43:53 · answer #4 · answered by Anonymous · 0 0

First, u do this: 3x -11 + 2x-2= 3x+2x -11-2
64= 5x-13
64+13=5x
5x= 77
x= 77/5

2007-02-01 15:39:56 · answer #5 · answered by Juni Mccoy 3 · 0 0

1. get all the similar terms together 64= (3x+2x) -11-2
2. 64 = 5x - 13 (adding all the terms together)
3 (+13 to both sides to get rid of -13) so 64+13 = 5x -13 +13
4 75 = 5x
5 (divide both sides by 5 to have X) 77/5 = 5x/5
6 therefore 15.4 = x

2007-02-01 15:43:46 · answer #6 · answered by lionelnz01 1 · 0 0

Brackets confuse things, and can mess with minus signs. Get rid of them first!
64= 3x - 11 + 2x - 2

Now, group the numbers and the x'es...
64 = 3x + 2x - 11 - 2

Now combine them-
64 = 5x - 13

Next step, move that 13 across-
64 + 13 = 5x
5x = 77

Finally, divide by 5-
x = 77/5 = 15.4

2007-02-01 15:40:36 · answer #7 · answered by Alan 6 · 0 0

64=(3x-11)+(2x-2)
(3*5=15) (2*31=62)
(15-11=4) (62-2=60)
(x=5) (x=31)

I dont know how right this, but it may help you to remember what to do. Good luck. D

2007-02-01 15:46:04 · answer #8 · answered by Anonymous · 0 1

I don't understand the difficulty in this equation.....
If i am right then ur solving for x.....
64=3x-11+2x-2 (i can remove paranthesis right??)
64=5x-13
x=77/5
x=15.4

2007-02-01 15:51:52 · answer #9 · answered by cosmos 2 · 0 0

The parenthese don't really apply here so you can take them away. Now combine like terms and solve for x:

64 = 5x - 13
77 = 5x
77/5 = x

2007-02-01 15:40:49 · answer #10 · answered by Anonymous · 0 0

fedest.com, questions and answers